INFLUENCE OF VARIABLE FLUID PROPERTIES, THERMAL RADIATION AND CHEMICAL REACTION ON MHD SLIP FLOW OVER A FLAT PLATE - Jana, Subrata; Das, Kalidas (Italian Journal of Pure and Applied Mathematics, 2015)
In the present study the magneto hydrodynamic (MHD) slip flow and heat transfer over a flat plate with convective surface heat flux at the boundary and temperature dependent fluid properties has been presented in presence of chemical reactions, thermal radiation and non-uniform heat source/sink. The transverse magnetic field is assumed as a function of the distance from the origin. Also it is assumed that the fluid viscosity and the thermal conductivity vary as an inverse function and linear function of temperature respectively. Using the similarity transformation, the governing system of equations are transformed into similarity non-linear ordinary diﬀerential equations which are solved numerically using symbolic software MATHEMATICA. As a result, the dimensionless velocity, temperature, concentration, the skin friction coeﬃcient, the Nusselt number and the local Sherwood number are presented through graphs and tables for several sets of values of the involved parameters of the problem and discussed in details from the physical point of view.